Peran Model Social Learning Dalam Meningkatkan Kompetensi Petani Garam di Kabupaten Pamekasan - Umi Hanik; Mutmainah Mutmainah (Universitas Trunojoyo Madura, 2018)
This study aims to determine the role of social learning models in improving the competency of salt farmers in Pamekasan Regency. The research approach used is qualitative research with grounded theory. Data collection techniques using depth interviews, observation and documentation studies. The results of the study showed that increasing the competency of salt farmers through social learning models was carried out by presenting examples of behavior from aspects: 1) knowledge (knowledge); 2) skills (skills); 3) self concept; 4) personal characteristics (traits); and 5) motives (motives). The role of the social learning model for increasing salt farmers in Pamekasan Regency is: 1) to increase knowledge so that farmers have several alternative ways to make salt to produce quality; 2) developing the competency of salt farmers through the delivery of information; 3) foster an attitude of helping others; and 4) fostering a cooperative attitude towards outside parties who wish to establish cooperation.